Cutaneous leishmaniasis in a renal transplant patient: Diagnostic challenges in a non-endemic setting - Zishan Nasir; Bushra M. Abdallah; Mohamed Aboukamar; Syed Hidayat Ali; Saifatullah Khan; Sulieman Abujarir; Muna Almaslamani; Muftah Othman (IDCases, 2025)
Leishmanial infections, though uncommon in Southeast and Central Asia, remain clinically significant due to their potential to cause substantial morbidity and mortality. This case report presents a young Nepalese male, four years post-renal transplant and with chronic allograft dysfunction secondary to non-compliance, who presented with a right chest skin lesion and fever. Initially suspected to be cutaneous tuberculosis or malignancy, investigations, including a skin biopsy, revealed cutaneous leishmaniasis. The patient responded well to treatment with liposomal amphotericin B, highlighting the importance of considering leishmaniasis in differential diagnoses, especially in immunocompromised individuals from, or travelling to, endemic regions.